Peran Financial Distress dalam Pengaruh Konservatisme Akuntansi terhadap Tax Avoidance - Gunarto, Natania Aurielle; Adi, Priyo Hari (E-Jurnal Akuntansi, 2022)
Many studies about the influence of accounting conservatism on tax avoidance have been carried out but have not considered the role of financial distress. This study aims to examine the influence of accounting conservatism on tax avoidance which is moderated by financial distress. This study is quantitative research on basic material companies listed on IDX from 2015 until 2019. A total of 56 samples from 95 populations were obtained by the purposive sampling technique. The data used is secondary data comprised of financial statements and annual reports from each company which will be analyzed using path analysis. The result shows that accounting conservatism has a positive but not significant on tax avoidance and financial distress is unable to moderate the influence of accounting conservatism on tax avoidance.  Keywords: Accounting Conservatism; Financial distress; Tax avoidance; Corporate Tax .